Analgesic efficacy in caesarean section: a comparison between fentanyl and buprenorphine as an adjuvant to bupivacaine under subarachnoid block - Nilotpal Das; Babita Lahkar; Himanjali Brahma; Bidyut Borah (Barpeta Obstetrics and Gynaecological Society, 2023)
Background and aims: Pain is a sensory modality as well as an experience. Both general and regional anaesthesia are used during caesarean sections. Present study was undertaken to compare the analgesic efficacy of intrathecal fentanyl and intrathecal buprenorphine as an adjuvant to bupivacaine in caesarean section under subarachnoid block. Methods: Hundred patients belonging to ASA II scheduled for caesarean section were randomly divided into two groups. Each group consisting of 50 patients, received 75 mcg of buprenorphine with 10mg of 0.5% hyperbaric bupivacaine (group BB) or 12.5 mcg of fentanyl with 10mg of 0.5% hyperbaric bupivacaine (group BF). The onset time and duration of sensory and motor block, maximum level of sensory block, duration of analgesia, two-point regression, hemodynamic changes and side effects were recorded. Results: Bupivacaine with buprenorphine had prolonged two segment regression (105.46±14.78 mins) and duration of analgesia (488.28±156.97 mins) compared to fentanyl (100.33±12.65 mins) and (210.32±8.10 mins) respectively. Onset of sensory (1.50±0.39 mins) and maximum sensory block upto T4 (4.00±0.98 mins) was faster in fentanyl compared to buprenorphine group (2.00±0.37 mins) and (4.56±1.14 mins) respectively. Hemodynamic changes and side effects in both the groups were comparable and statistically insignificant. Conclusion: The study thus concluded that although fentanyl produced faster sensory block, duration of analgesia was longer with buprenorphine, and both the drugs did not cause significant side effects.